Applied Behavioral Science In Urban Administrative/Political Systems. - Eddy, William B.; Saunders, Robert J. (Public Administration Review)
Methods of organization improvement derived from the applied behavioral sciences may be of benefit to local government However, there are potential conflicts between the behavioral science models of desirable organizations and change processes and the realities of administrative systems imbedded in political processes. In programs to apply organization development or other behavioral science methods in public organizations these conflicts need to be identified and understood.